Enhance of ship safety based on maintenance strategies by applying of Analytic Hierarchy Process - Dagkinis, Ioannis; Nikitakos, Nikitas (SPOUDAI Journal of Economics and Business, 2013)
The equipment maintenance strategy is one of the factors influencing the safety and overall operational management of the ship. Using the wrong maintenance strategies can waste time, money, and resources, and often has no effect on improving or maintaining availability of equipments. Thus the reliability of the ship is reduced, and the risks and the probability of failures increased. The aim of this paper is to show one approach to the risk evaluation from equipments maintenance strategy of the ship. The paper describes main characteristics of Maintenance Strategies where the impact on safety is crucial and a model for evaluation of its risk. The model is based on the application of the Analytic Hierarchy Process method. The developed model uses subjectivity, experience and knowledge, when determining significance of selected risk elements in relation to total safety and risk. JEL Classification: C670; C830.